2010
DOI: 10.1094/mpmi-23-3-0340
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Deficiency in Arabidopsis Induces Constitutive Priming That is Dependent on Hydrogen Peroxide, Salicylic Acid, and the NPR1 Gene

Abstract: The ascorbic acid (AA)-deficient Arabidopsis thaliana vtc1-1 mutant exhibits increased resistance to the virulent bacterial pathogen Pseudomonas syringae. This response correlates with heightened levels of salicylic acid (SA), which induces antimicrobial pathogenesis-related (PR) proteins. To determine if SA-mediated, enhanced disease resistance is a general phenomenon of AA deficiency, to elucidate the signal that stimulates SA synthesis, and to identify the biosynthetic pathway through which SA accumulates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 94 publications
3
67
1
Order By: Relevance
“…Previous research has shown that fruit was able to mount a rapid and efficient defense response and to maintain a generally higher L-AsA content after being infected by B. cinerea (Davey et al, 2007), which is in accordance with results of the present study. In contrast, the AsA-deficient A. thaliana VTC1, VTC2, VTC3, and VTC4 mutants were more resistant to P. syringae relative to the wild-type (Pavet et al, 2005;Mukherjee et al, 2010).…”
Section: The Roles Of Asa During Pathogenesismentioning
confidence: 81%
“…Previous research has shown that fruit was able to mount a rapid and efficient defense response and to maintain a generally higher L-AsA content after being infected by B. cinerea (Davey et al, 2007), which is in accordance with results of the present study. In contrast, the AsA-deficient A. thaliana VTC1, VTC2, VTC3, and VTC4 mutants were more resistant to P. syringae relative to the wild-type (Pavet et al, 2005;Mukherjee et al, 2010).…”
Section: The Roles Of Asa During Pathogenesismentioning
confidence: 81%
“…As H 2 O 2 acts synergistically with salicylic acid to induce plant defense responses (Neuenschwander et al, 1995;Sharma et al, 1996;Alvarez et al, 1998;Mukherjee et al, 2010), we measured salicylic acid concentrations in response to DC3000 infection. Although P. syringae infiltration into Arabidopsis leaves significantly increased the concentration of salicylic acid 2 d later, there was no significant difference in the free or total salicylic acid content of wild-type and nata1 leaves ( Fig.…”
Section: Arabidopsis Nata1 Functions As a Putrescine Acetyltransferasementioning
confidence: 99%
“…Salicylic acid and H 2 O 2 act synergistically to initiate both local and systemic plant responses to pathogen infection (Neuenschwander et al, 1995;Sharma et al, 1996;Alvarez et al, 1998;Mukherjee et al, 2010). A rapid increase in H 2 O 2 production, initiated through the activity of NADPH oxidase, occurs as a hypersensitive response to pathogen infection in many plant species (Lamb and Dixon, 1997;Torres et al, 2005).…”
mentioning
confidence: 99%
“…The regulation of this loop is linked to the glutathioneascorbate cycle. For instance, the ascorbate-deficient vitamin C mutants hyperaccumulate constitutively both SA and hydrogen peroxide (Mukherjee et al, 2010). In addition, a study using Arabidopsis mutants catalasedeficient2 and glutathione-deficient cadmium-sensitive2 indicates that the cellular glutathione redox status is a key player linking intracellular hydrogen peroxide with the activation of the SA pathway (Han et al, 2013).…”
Section: Oglci3f Is a Product Of Ig Metabolism And Directly Linked Tmentioning
confidence: 99%